1997
DOI: 10.1093/ps/76.9.1239
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of fumonisin B1 present in Fusarium moniliforme culture material and T-2 toxin or deoxynivalenol in broiler chicks

Abstract: The individual and combined effects of feeding diets containing 300 mg fumonisin B1 (FB1), and 5 mg T-2 toxin (T-2)/kg of diet, or 15 mg/kg deoxynivalenol (DON, vomitoxin) from naturally contaminated wheat were evaluated in two studies in male broiler chicks from day of hatch to 19 or 21 d of age in Experiments 1 and 2, respectively. When compared with controls, body weight gains were reduced 18 to 20% by FB1, 18% by T-2, 2% by DON, 32% by the FB1 and T-2 combination, and 19% by the FB1 and DON combination. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
2
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 58 publications
12
64
2
5
Order By: Relevance
“…In another work the same authors (Huff et al, 1988b) evaluated this mycotoxin combination as one of the most effective among mycotoxin combinations tested in pigs and poultry. Kubena et al (1997) found an increased effect of fumonisin B 1 and T-2 toxin combination on the basis of some indicators (feed intake, mortality, stomach and pancreas relative weight), although these toxins affected antagonistically, for example, oral lesions. The results of our observations show certain differences in the method of influencing individual monitored parametres.…”
Section: Resultsmentioning
confidence: 96%
“…In another work the same authors (Huff et al, 1988b) evaluated this mycotoxin combination as one of the most effective among mycotoxin combinations tested in pigs and poultry. Kubena et al (1997) found an increased effect of fumonisin B 1 and T-2 toxin combination on the basis of some indicators (feed intake, mortality, stomach and pancreas relative weight), although these toxins affected antagonistically, for example, oral lesions. The results of our observations show certain differences in the method of influencing individual monitored parametres.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, additive or even synergistic effects on feed intake cannot be ruled out in studies based on the feeding of Fusarium-contaminated grain to pigs. It now also appears that NIV and DAS reduce feed intake in broiler chickens (Table 2) whereas DON has no effect on feed intake or growth (Kubena et al, 1997a). In mink, feed choice is affected by levels of DON as low as 0.28 mg/kg diet (Gibson et al, 1993).…”
Section: Jpf D'mello Et Al / Animal Feed Science and Technology 8mentioning
confidence: 99%
“…1). In addition, a feature of at least two trichothecenes (DON and T-2 toxin) is their ability to impair immunocompetence, a property which may well be associated with other mycotoxins in this group (Kubena et al, 1997a;Vanyi et al, 1994b). Furthermore, in sows, T-2 toxin may cause infertility, and after parenteral administration during the last trimester of gestation, is able to precipitate abortion within 48 h (Weaver et al, 1986).…”
Section: Trichothecenesmentioning
confidence: 99%
“…A combination of ZEN and fusaric acid increases the concentration in rat milk of each of these compounds by a factor of two to five [65]. An interaction between FB1 and DON increases the amount of blood protein whereas an interaction between FB1 and T-2 toxin leads to an increase in plasma calcium concentration in the chicken [36] or to an increase in haemoglobin and haematocrit concentration in turkeys [35]. Even though body weight is reduced by 18 to 20% in chickens receiving a feed contaminated with 300 mg FB1 per kg feed for 20 days after birth, body weight is reduced by 18% when 5 mg T-2 is added per kg of feed, by 2% when 15 mg DON is added per kg, by 32% when both FB1 and T-2 are added, and by 19% when both FB1 and DON are added [36].…”
Section: Synergy Between Mycotoxinsmentioning
confidence: 99%
“…An interaction between FB1 and DON increases the amount of blood protein whereas an interaction between FB1 and T-2 toxin leads to an increase in plasma calcium concentration in the chicken [36] or to an increase in haemoglobin and haematocrit concentration in turkeys [35]. Even though body weight is reduced by 18 to 20% in chickens receiving a feed contaminated with 300 mg FB1 per kg feed for 20 days after birth, body weight is reduced by 18% when 5 mg T-2 is added per kg of feed, by 2% when 15 mg DON is added per kg, by 32% when both FB1 and T-2 are added, and by 19% when both FB1 and DON are added [36]. In turkeys, in the same conditions, 300 mg FB1 reduced weight gain by 24 to 30%, 4 mg DAS reduced it by 30%, 3 mg OTA reduced it by 8%, a combination of FB1 and DAS reduced it by 46%, and a combination of FB1 and OTA reduced it by 37% [37].…”
Section: Synergy Between Mycotoxinsmentioning
confidence: 99%